Effective Combinations of Immunotherapy and Radiotherapy for Cancer Treatment - Yu, Siting; Wang, Yang; He, Ping; Shao, Bianfei; Liu, Fang; Xiang, Zhongzheng; Yang, Tian; Zeng, Yuanyuan; He, Tao; Ma, Jiachun; Wang, Xiran; Liu, Lei (Frontiers in Oncology, 2022)
Though single tumor immunotherapy and radiotherapy have significantly improved the survival rate of tumor patients, there are certain limitations in overcoming tumor metastasis, recurrence, and reducing side effects. Therefore, it is urgent to explore new tumor treatment methods. The new combination of radiotherapy and immunotherapy shows promise in improving therapeutic efficacy and reducing recurrence by enhancing the ability of the immune system to recognize and eradicate tumor cells, to overcome tumor immune tolerance mechanisms. Nanomaterials, as new drug-delivery-system materials of the 21st century, can maintain the activity of drugs, improve drug targeting, and reduce side effects in tumor immunotherapy. Additionally, nanomaterials, as radiosensitizers, have shown great potential in tumor radiotherapy due to their unique properties, such as light, heat, electromagnetic effects. Here, we review the mechanisms of tumor immunotherapy and radiotherapy and the synergies of radiotherapy with multiple types of immunotherapies, including immune checkpoint inhibitors (ICIs), tumor vaccines, adoptive cell therapy, and cytokine therapy. Finally, we propose the potential for nanomaterials in tumor radiotherapy and immunotherapy.